Painless spelling - Mary Elizabeth (Mary Elizabeth Podhaizer) (Hauppage, N.Y. : Barrons Educational Series, Inc., 2011)
Analyzes sound and letter patterns, diphthongs, silent letters, homophones and homographs, compound and abbreviated words, contractions, prefixes, suffixes, and base words to teach spelling skills.
Includes index.
Keywords: English language -- Orthography and spelling -- Study and teaching (Elementary).; English language -- Orthography and spelling -- Study and teaching (Middle school).; English language -- Spelling